Mekanisme Dan Proteksi Jaminan Nasabah Pada Gadai Informal - Yuri Nanda Larasati; Jafril Khalil (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2017)
Regulation of the financial services authority (OJK) No. 31/POJK.05/2016 on Venture had arranged that the financial services agency on the basis of the law of pledge is in coaching and supervision OJK. Yet the existence of laws – invitation to Governing Enterprise pawn shops causing business activities conducted by the above parties are not yet regulated. The condition is feared could cause harm to the consumer society. The purpose of this research is to know the procedures, mechanisms, protection of goods and guarantee the consumer on an informal pledge financing, methods of determination of the cost of maintenance of the goods and the goods of the execution mechanism of the pledge as well as protection for the collateral items are viewed from the side of the consumer by looking at laws-invitations and Sharia. To find out whether the pledge have gotten permission from OJK. This research uses qualitative research methods with the study of library research, field data and simulations. The approach used in this study is the empirical juridical approach. Elaboration upon the results is discussed further in this article.